Monitoring of Cell‐Dependent Reduced States Using Aptamer‐Functionalized Reduction‐Sensitive Quantum Dots. (18th December 2020) - Lee, Gwan‐Ho; Kang, Sung Muk; Lee, Soo Bin; Lee, Dohyun; Ko, Youngkuk; Nam, Jungyeon; Jo, Juhyun; Hah, Sang Soo
Abstract : Conjugation of quantum dot (QD) with oxidized nile blue (NB) is known to be able to strongly decrease fluorescence intensity of QD. In the present study, NB‐conjugated QD (QD‐NB) was functionalized with anti‐human epidermal growth factor receptor 2 aptamer to form aptamer‐functionalized QD‐NB (Apt‐QD‐NB), as a new biosensing platform to monitor aptamer‐dependent internalizations and reduction‐dependent transformations. Our study shows that more QD fluorescence signals in cells can be induced by the specific internalization of higher amounts of Apt‐QD‐NB and that the higher ratio of reduced NB over oxidized NB resulting from the different reducing environment of the cells can lead to brighter QD signals. Apt‐QD‐NBs are expected to be used as optical labels that can monitor intracellular metabolic pathways at the single‐cell level, because the use of Apt‐QD‐NBs to investigate drug effectiveness and cellular redox conditions offers exciting opportunities for drug screening. Abstract : Aptamer‐functionalized reduction‐sensitive quantum dot‐nile blue system for monitoring of cell‐dependent reduced states.